Pembaharuan Hukum Islam - Nurhuda, Rohmad (El-Dusturie, 2022)
Noel J. Coulson identifies four distinct historical manifestations of the rise of Islamic law: first, the incorporation of the siyasa doctrine, which required the codification (grouping of similar laws into legal books) of Islamic law into state statutes. Second, Muslims are not required to follow a particular madhhab; this is what he calls the doctrine of superstition (selection), which determines which schools of thought are most widely accepted. As a third point, "tatbiq doctrine" (law application to new events) alludes to the creation of law before the emergence of new legal events. Fourth, he defines the process of transforming law from traditional to modern forms as "Tajdid doctrine" (reinterpretation).Noel J. Coulson mengidentifikasi empat manifestasi historis yang berbeda dari kebangkitan hukum Islam: pertama, penggabungan doktrin siyasah, yang memerlukan kodifikasi (pengelompokan hukum serupa ke dalam buku hukum) hukum Islam ke dalam undang-undang negara. Kedua, Muslim tidak diharuskan mengikuti mazhab tertentu; inilah yang dia sebut sebagai doktrin takhayyur (seleksi), yang menentukan aliran pemikiran mana yang paling banyak diterima. Sebagai poin ketiga, "doktrin tathbiq" (penerapan hukum pada peristiwa baru) menyinggung penciptaan hukum sebelum munculnya peristiwa hukum baru. Keempat, ia mendefinisikan proses transformasi hukum dari bentuk tradisional ke bentuk modern sebagai "doktrin Tajdid" (reinterpretasi).